There ain't no plantations in Pittsburgh: glimpses of the African diaspora in the plays of August Wilson - Hull, Brian J., author; Thompson, Deborah, advisor; Harding, Blane, committee member; Hentschell, Roze, committee member (Colorado State University. Libraries, 2010)
"There Ain’t no Plantations in Pittsburgh" addresses questions of African identity versus European identity for African Americans as addressed by the plays of August Wilson. Whereas characters who embrace an African ethos in Wilson's plays are prominent, they are not necessarily more enlightened than their apparently less African counterparts. Instead of resorting to overly simplistic formulas for black liberation, Wilson, in plays like Seven Guitars, Ma Ramey's Black Bottom, Joe Turner’s Come and Gone, and Two Trains Running, depicts the complex psychological landscape of twentieth century America where African roots prove elusive and the "names of the gods have been forgotten." In Wilson's dramaturgy echoes of the brutal history of slavery and the Middle Passage coincide with the burgeoning possibilities of renewed dignity and a distinctive African American voice. History constantly interacts with the present and cannot be seen as finished or insignificant but instead is a vital part of an ever evolving reality where the past most be confronted to make room for the future.
Covers not scanned.
Keywords: African diaspora in literature